The Organizational Attachment Survey: Instrument Development and Exploratory Factor Analysis - KHATRI, PUJA; VERMA, NEHA (International Journal of Psychosocial Rehabilitation, 2020)
Organizational attachment is a stabilizing psychological force that ties an individual to an organization. It is a well-established fact that organizational attachment is very essential for the organization to decrease the attrition and to strengthen the commitment of the employee towards the organization. Despite the role of organizational attachment being so prominent in the organizations, it is ironic that most of the studies have been conducted in western countries only; whereas, in India, the concept is relatively new. Furthermore, there is a lack of validated measurement of the construct. Therefore, the purpose of the present study is to explore and validate the major dimensions of organizational attachment by using the Principal component analysis technique. 231 respondents were selected from the population of IT/ITES sector professionals in the Delhi/NCR region, India to answer a self-developed instrument. The study has successfully identified four factors with 65 % percent of the total variance explained. Cronbach Alpha of the same came out to be 0.847.